2015
DOI: 10.1002/qj.2598
|View full text |Cite|
|
Sign up to set email alerts
|

Atmospheric ions and new particle formation events at a tropical location, Pune, India

Abstract: Characteristics of small, intermediate and large ions and nanometre particles, and the influences of environmental conditions and local topography on the interactions of these ions and particles in the size range of 3.85-47.8 nm diameter are studied during new particle formation (NPF) events observed at Pune, India from 20 March to 23 May 2012. During the NPF events, the formation rate of 5 nm particles ranged from 3.5 to 13.9 cm −3 s −1 and growth rates of both positive and negative ions were greater than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 112 publications
1
27
0
Order By: Relevance
“…Regarding ambient measurements, simultaneous measurements of sulfuric acid, sub-3 nm particles, and oxidation products of BVOCs are very limited. However, observations have shown that even at temperatures above 300 K and at high RH above 60%, NPF still takes place at various atmospheric environments under high CS conditions, such as in Ohio, Taiwan, China, India, and the Mediterranean [Erupe et al, 2010;Kalivitis et al, 2015;Kamra et al, 2015;Kanawade et al, 2012Kanawade et al, , 2014Qi et al, 2015;Young et al, 2013]. In Kent (Ohio), NPF took place during the summer with moderate sulfuric acid concentrations (at 10 6 cm À3 ), and the NPF days had warmer temperatures (>300 K) than the non-NPF days [Erupe et al, 2010;Kanawade et al, 2012].…”
Section: Comparison With Laboratory Studies and Other Field Observationsmentioning
confidence: 99%
“…Regarding ambient measurements, simultaneous measurements of sulfuric acid, sub-3 nm particles, and oxidation products of BVOCs are very limited. However, observations have shown that even at temperatures above 300 K and at high RH above 60%, NPF still takes place at various atmospheric environments under high CS conditions, such as in Ohio, Taiwan, China, India, and the Mediterranean [Erupe et al, 2010;Kalivitis et al, 2015;Kamra et al, 2015;Kanawade et al, 2012Kanawade et al, , 2014Qi et al, 2015;Young et al, 2013]. In Kent (Ohio), NPF took place during the summer with moderate sulfuric acid concentrations (at 10 6 cm À3 ), and the NPF days had warmer temperatures (>300 K) than the non-NPF days [Erupe et al, 2010;Kanawade et al, 2012].…”
Section: Comparison With Laboratory Studies and Other Field Observationsmentioning
confidence: 99%
“…The electrical sources in the lower atmosphere are thunderstorms, shower clouds, point discharge currents, ionization by radon isotopes and galactic cosmic rays Siingh et al, 2013c;Kamra et al, 2015). The circuit closes through fairweather current remote from the source/generator.…”
Section: Global Electric Circuitsmentioning
confidence: 99%
“…This site has no major industrial activities within ∼5 km radius but several large industrial facilities are located to the west and north within a radius of 300 km. The climate of Pune is semi-arid bordering on tropical wet and dry, with daily mean temperatures ranging between 20 and 28 • C. A detailed description of the observation site is given by Siingh et al (2013) and Kamra et al (2015).…”
Section: Observation Site and Instrumentationmentioning
confidence: 99%
“…Another long time series of more than 10 years of measurements with a variety of instruments at Hyytiälä, Finland, substantially added to our understanding of the nucleation and growth processes of ions/particles in the atmosphere (Laakso et al, 2004b;Kulmala et al, 2005Kulmala et al, , 2007Hirsikko et al, 2011). Since then, several studies of simultaneous measurements of atmospheric ion concentration and their mobility spectra using ion spectrometers with much higher mobility resolution of 20 mobility ranges have been conducted at different locations such as at the Mace Head research station on the west coast of Ireland (Vana et al, 2008) in the range of 0.0013-3.2 cm 2 s −1 volt −1 , at Jungfraujoch, Switzerland , at a tropical station Pune, India (Siingh et al, 2013 ;Kamra et al, 2015) in the range of 0.00133-3.16 cm 2 s −1 volt −1 , and at Nanjing in China (Huang et al, 2016). Further, Manninen et al (2010) have reported measurements of ∼1-42 nm particles at twelve European sites.…”
Section: Introductionmentioning
confidence: 99%